Carbon dioxide capture system, reactor and filler used therein

By using modified foam fillers in the micro-filled bed reactor of the carbon dioxide capture system, the problem of MDEA amine liquid foaming is solved, and the capture efficiency and mass transfer efficiency of carbon dioxide are improved.

CN118558111BActive Publication Date: 2025-04-01BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410520046.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-28
Publication Date
2025-04-01
Estimated Expiration
2044-04-28

AI Technical Summary

Technical Problem

In the existing carbon dioxide capture system, MDEA amine liquid is prone to foaming, resulting in a decrease in mass transfer efficiency and low capture efficiency.

Method used

Foam fillers prepared by specific preparation methods are used to improve the hydrophobicity of the pore surface and form inorganic nanoparticles of specific particle sizes on the pore surface, enhancing the gas-liquid mass transfer performance, reducing foam stability, and thus reducing foaming.

Benefits of technology

It effectively reduces the bubbles of the amine liquid, improves the capture efficiency of carbon dioxide, improves the mass transfer efficiency, and is suitable for various types of carbon capture scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118558111B_ABST
    Figure CN118558111B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon dioxide capture system, a reactor and a filler used therein, and relates to the field of carbon dioxide capture. The carbon dioxide capture system comprises: a gas supply unit for providing a mixed gas containing carbon dioxide to be captured; an absorbent supply unit for providing an absorbent; a mixing unit for mixing the mixed gas and the absorbent; a micro-packed bed reactor filled with a foam filler; and a method for preparing the foam filler comprising the following steps: (1) providing metal foam; (2) mixing a first catecholamine solution with a buffer solution to obtain a first modified liquid; (3) mixing the first modified liquid and the metal foam in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a first preset time, and performing solid-liquid separation to obtain a first intermediate; (4) mixing inorganic nanoparticles, a solvent, and a fluorinated silane coupling agent for a second preset time to obtain a second modified liquid; and (5) mixing the second modified liquid and the first intermediate in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a third preset time to obtain the foam filler. The carbon dioxide capture system of the present invention has high capture efficiency, less foaming of the amine liquid and fast defoaming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon dioxide capture, and in particular to a carbon dioxide capture system, a reactor and a filler used therein. Background Art

[0002] The capture and removal of carbon dioxide is a core process in many industrial fields, such as the deacidification process in the natural gas industry, the decarbonization of coke oven gas, the decarbonization of urban gas, the decarbonization of coal-fired flue gas, and the recovery of oilfield produced gas. Achieving efficient carbon capture is of great significance for reducing carbon emissions and improving resource utilization efficiency. Existing carbon dioxide capture technologies include physical adsorption, membrane separation, and solvent absorption. Among them, the alcohol amine solvent absorption method based on N-methyldiethanolamine (MDEA) has the advantages of low solution viscosity, low operating cost, high CO2 capacity, and low regeneration energy consumption, and is widely used. However, the mixed solution based on MDEA has the disadvantage of easy foaming, and the foam has strong stability, which leads to the entrainment of mist and foam, resulting in an increase in the loss of amine liquid and a decrease in carbon capture efficiency. In the prior art, this problem is often solved by adding a defoamer to the amine liquid, but on the one hand, the defoamer will affect the stability of the system operation and the solution will clog the equipment; on the other hand, the defoamer often needs to be added regularly, which is troublesome to operate. Another way to solve the foaming problem is to use a compound decarburizing agent, such as CN101822932B, which uses a compound activator (piperazine, N-methyl monoethanolamine and diglycolamine), which effectively improves the anti-foaming performance. Another common way to solve the foaming problem is to strengthen the filtration of gas and amine liquid to avoid bringing in impurities, causing bubbles, or making the bubbles stable for too long.

[0003] On the other hand, micro-packed bed reactors are considered to have great advantages in the field of carbon dioxide capture due to their high mass transfer efficiency, fast heat removal rate and plug flow, as well as the advantages of easy fixation of catalytic fillers, continuous operation and intrinsic safety of traditional fixed bed reactors. In micro-packed beds, micro-sized fillers are core components, among which micro-sized metal foam fillers are a type of filler that is widely used. However, when the inventors applied micro-packed bed reactors to carbon capture experiments, they found that the micro-channel structure of micro-sized metal foam fillers would make the foaming phenomenon of MDEA amine liquid more serious, which would lead to lower mass transfer efficiency than traditional fixed bed reactors, making it difficult to achieve the theoretically predicted results. The mass transfer and reaction intensification strategies of the current common micro-packed bed reactors are mainly through changing the gas-liquid distribution structure of the reactor, reducing the filler pore size, increasing the fluid flow rate, etc., but this will complicate the reactor structure and increase energy consumption. Moreover, the inventors found that after further reducing the filler pore size, the foaming phenomenon of the amine liquid became more serious. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a carbon dioxide capture system, which can effectively reduce amine liquid bubbles and improve carbon dioxide capture efficiency.

[0005] Another technical problem to be solved by the present invention is to provide a reactor used in a carbon dioxide capture system, which can improve the capture efficiency of carbon dioxide.

[0006] Another technical problem to be solved by the present invention is to provide a reactor filler used in a carbon dioxide capture system, which can improve the capture efficiency of carbon dioxide.

[0007] In order to solve the above technical problems, as a first aspect of the present invention, the present invention provides a carbon dioxide capture system, which comprises:

[0008] A gas supply unit, used for providing a mixed gas containing carbon dioxide to be captured;

[0009] An absorbent providing unit, used for providing an absorbent, wherein the absorbent is an amine absorbent;

[0010] a mixing unit for mixing the mixed gas and the absorbent; and

[0011] A micro-packed bed reactor filled with foam fillers;

[0012] The preparation method of the foam filler comprises the following steps:

[0013] (1) providing a metal foam; wherein the average pore size of the metal foam is 50 to 800 μm;

[0014] (2) mixing the first catecholamine solution with a buffer solution to obtain a first modified solution; wherein the concentration of catecholamines in the first catecholamine solution is 0.5 to 5 g / L;

[0015] (3) mixing the first modified liquid and the metal foam in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a first preset time, and performing solid-liquid separation to obtain a first intermediate;

[0016] (4) mixing the inorganic nanoparticles, the solvent, and the fluorinated silane coupling agent for a second preset time to obtain a second modified solution; wherein the concentration of the inorganic nanoparticles in the second modified solution is 1 to 10 g / L, and the concentration of the fluorinated silane coupling agent is 0.2 to 2 vol%; and the maximum particle size of the inorganic nanoparticles is ≤500 nm;

[0017] (5) The second modified liquid and the first intermediate are mixed in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a third preset time to obtain a foam filler.

[0018] On the one hand, a micro-packed bed reactor is introduced into the carbon dioxide capture system of the present invention, which has a high mass transfer efficiency and can effectively improve the capture efficiency of carbon dioxide. On the other hand, the micro-packed bed reactor of the present invention uses a foam filler prepared by a specific preparation method. Through this preparation method, on the one hand, the hydrophobicity of the surface of the foam filler pores is greatly improved, and the gas-liquid mass transfer performance is enhanced; at the same time, the more hydrophobic pores can increase the liquid flow rate of the water film on the foam surface (i.e., the gas-liquid interface), reduce the foam stability, thereby reducing foaming and shortening the defoaming time. Secondly, by forming inorganic nanoparticles of a specific particle size on the surface of the foam filler pores, the disturbance of the liquid flow distribution is improved, making the foam easier to eliminate, and controlling the particle size of the inorganic nanoparticles can also prevent excessive nanoparticles from accumulating and affecting the gas-liquid mass transfer performance. Thirdly, by using polycatecholamine substances to organically adhere to the surface of the metal foam pores and composite inorganic nanoparticle coating, the mechanical stability of the entire coating is improved, and the acid and alkali resistance of the metal foam is improved, making it suitable for various types of carbon capture scenarios. Specifically, the carbon capture system of the present invention can be used for the absorption and treatment of carbon dioxide in flue gas, refinery gas, natural gas, synthesis gas, conversion gas and other gases.

[0019] It should be noted that the relationship between weight parts and volume parts in the present invention is g / mL, or a corresponding relationship obtained by proportionally enlarging or reducing the corresponding relationship, such as mg / μL, kg / L, t / m 3 etc., but not limited to.

[0020] Specifically, in some embodiments of the present invention, the metal foam is selected from one or more of foamed nickel, foamed iron, foamed nickel copper, and foamed copper, but is not limited thereto. Preferably, the metal foam is foamed nickel or foamed nickel copper, which has strong corrosion resistance, especially strong corrosion resistance to mixed gas containing carbon dioxide.

[0021] Specifically, in some embodiments of the present invention, the average pore size of the metal foam is 50-800 μm. Preferably, the average pore size of the metal foam is 100-500 μm.

[0022] Specifically, in some embodiments of the present invention, the catecholamine is selected from one or more of dopamine, levodopa, and norepinephrine; by mixing the catecholamine solution with the buffer, polycatecholamine can be formed, which greatly improves the adhesion of inorganic nanoparticles to metal foam, avoids the inorganic nanoparticles being dispersed into the amine solution under high operating pressure, and avoids the inorganic nanoparticles prolonging the foam bursting time and the defoaming time. Preferably, the catecholamine is selected from dopamine or levodopa.

[0023] Specifically, in some embodiments of the present invention, the concentration of catecholamines in the first catecholamine solution is 0.5 to 5 g / L, preferably 0.5 to 4 g / L.

[0024] Specifically, in some embodiments of the present invention, the buffer solution is selected from tris(hydroxymethyl)aminomethane hydrochloric acid solution or sodium hydroxide solution; specifically, the concentration of tris(hydroxymethyl)aminomethane hydrochloric acid solution is 0.1-1 mol / L; the concentration of sodium hydroxide solution is 0.1-1 mmol / L; the volume ratio of the buffer solution to the first catecholamine solution is 0.1-1.5:100.

[0025] Specifically, in some embodiments of the present invention, the first preset time is 5 to 50 hours, and the buffer solution and the first catecholamine solution are mixed at room temperature (10 to 35° C.).

[0026] Specifically, in some embodiments of the present invention, the inorganic nanoparticles are selected from one or more of nano-silicon dioxide, nano-γ-alumina, nano-cerium oxide or nano-titanium dioxide, but are not limited thereto. Preferably, the inorganic nanoparticles are selected from nano-silicon dioxide or nano-γ-alumina.

[0027] Specifically, in some embodiments of the present invention, the maximum particle size of the inorganic nanoparticles is ≤500 nm, and preferably, the particle size is 5 to 300 nm.

[0028] Specifically, in some embodiments of the present invention, the concentration of the inorganic nanoparticles in the second modifying solution is 1 to 10 g / L, preferably 1 to 5 g / L.

[0029] Specifically, in some embodiments of the present invention, the solvent is selected from one or more of water, methanol, ethanol, and propanol, but is not limited thereto.

[0030] Specifically, in some embodiments of the present invention, the silane coupling agent is a fluorinated methoxysilane coupling agent or a fluorinated ethoxysilane coupling agent, which can not only effectively improve the hydrophobicity of the inorganic nanoparticles, but also achieve a stable connection with the polycatecholamine. Specifically, the silane coupling agent can be one or more of heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, or tridecafluorooctyltrimethoxysilane, but is not limited thereto.

[0031] Specifically, in some embodiments of the present invention, the concentration of the fluorine-containing silane coupling agent in the second modifying liquid is 0.2 to 2 vol%, preferably 1 to 2 vol%.

[0032] Specifically, in some embodiments of the present invention, the second preset time is 0.5 to 5 hours, preferably 1 to 4 hours. The mixing temperature is room temperature (10 to 35° C.).

[0033] Specifically, in some embodiments of the present invention, the third preset time is 1 to 12 hours, preferably 1 to 10 hours. The mixing temperature is room temperature (10 to 35° C.).

[0034] Preferably, in some embodiments of the present invention, the metal foam is nickel foam, which has strong corrosion resistance.

[0035] Preferably, in some embodiments of the present invention, the catecholamine is levodopa, which can further enhance the adhesion of the inorganic nanoparticles and optimize the acid and alkali corrosion resistance of the metal foam.

[0036] Preferably, in some embodiments of the present invention, the buffer solution is a sodium hydroxide solution.

[0037] Preferably, in some embodiments of the present invention, the inorganic nanoparticles are nano-γ-alumina.

[0038] Preferably, in some embodiments of the present invention, the solvent is a mixture of water and ethanol, and the volume ratio of water to ethanol is 2 to 4:1. Based on the above solvent, the dispersion of inorganic nanoparticles in the second modified liquid can be improved, providing a good basis for uniform loading.

[0039] Preferably, in some embodiments of the present invention, the silane coupling agent is heptadecafluorodecyltrimethoxysilane.

[0040] Preferably, in some embodiments of the present invention, the average pore size of the metal foam is 150-300 μm; the average particle size of the inorganic nanoparticles is 10-200 nm. Based on the above metal foam and inorganic nanoparticles, the foaming possibility can be further reduced and the defoaming time can be shortened.

[0041] Preferably, in some embodiments of the present invention, in step (1), the metal foam is washed with water, ethanol, hydrochloric acid and water in sequence to remove impurities attached to the inside of the metal foam pores and optimize the subsequent adhesion of polycatecholamine and inorganic nanoparticles.

[0042] Preferably, in some embodiments of the present invention, the concentration of catecholamines in the first catecholamine solution is 1.5 to 3 g / L; the volume ratio of the buffer solution to the first catecholamine solution is 0.3 to 1:100. Based on the above concentration and ratio control, the adhesion performance of the inorganic nanoparticles can be further optimized.

[0043] Preferably, in some embodiments of the present invention, in step (3), the first modifying liquid and the metal foam are mixed in a ratio of 200 to 400 parts by volume: 4 to 9 parts by weight, stirred and immersed at a speed of 300 to 900 rpm for 6 to 48 hours, and the solid phase obtained after solid-liquid separation is washed with water and dried to obtain the first intermediate.

[0044] Preferably, in some embodiments of the present invention, in step (4), the inorganic nanoparticles and the solvent are mixed at a speed of 500 to 900 rpm for 1 to 2 hours, and ultrasonically dispersed for 0.5 to 1 hour, and then a silane coupling agent is added and mixed at a speed of 500 to 900 rpm for 10 to 30 minutes to obtain a second modified solution;

[0045] Preferably, in some embodiments of the present invention, in step (5), the second modified liquid and the first intermediate are mixed in a ratio of 200 to 400 parts by volume: 2 to 7 parts by weight, and grafted at a rotation speed of 300 to 700 rpm for 2 to 10 hours. After solid-liquid separation, the solid phase obtained is washed with water and dried to obtain a foam filler.

[0046] Preferably, in one embodiment of the present invention, step (3) comprises:

[0047] (3.1) mixing the first modified liquid and the metal foam in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a first preset time, and performing solid-liquid separation to obtain a second intermediate;

[0048] (3.2) mixing the second catecholamine solution with the metal salt to obtain a third modified solution;

[0049] (3.3) The third modified liquid and the second intermediate are mixed in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight, and ultrasonically treated for a fourth preset time to obtain a first intermediate by solid-liquid separation.

[0050] It should be noted that the inventors found during the research that when only the first modified liquid was used to load polycatecholamine on the surface of the metal foam, the surface was prone to partial agglomeration (see Figure 4); According to the analysis of the inventors, this is because catecholamines have not been completely polymerized in the buffer solution, and some oligomers exist. These oligomers agglomerate on the mesh surface of the metal foam mesh, resulting in a decrease in the uniformity of the inorganic nanoparticles subsequently loaded, and the inability to completely protect the polycatecholamine layer, which reduces the acid and alkali resistance and erosion resistance of the foam filler and shortens its service life. Therefore, in a preferred embodiment of the present invention, the metal foam is first dip-coated with a first modified liquid obtained by mixing a first catecholamine solution with a buffer solution, and then mixed with a third modified liquid obtained by mixing a second catecholamine solution with a metal salt, and ultrasonically treated, so that the oligomers are separated from the metal foam surface under the action of ultrasound, and are quickly polymerized under the action of metal ions. Through the above-mentioned coating method, the uniformity of the load of the polycatecholamine layer is effectively improved ( Figure 3 ), thereby effectively improving the foam filler's ability to resist acid, alkali and erosion.

[0051] Specifically, in some embodiments of the present invention, in step (3.2), the metal ion is Fe 2+ , Fe 3 + , Cu 2+ 、Zn 2+ One or more of the above metal ions can quickly promote the polymerization of catecholamine oligomers to form polymers. Preferably, in one embodiment of the present invention, the metal ion is Fe 2+ and Cu 2+ A mixture of the two, and the molar ratio of the two is 1:1-2.

[0052] Specifically, in some embodiments of the present invention, in step (3.2), the concentration of metal ions is 5×10 -4 ~1×10 -2 mol / L, preferably 5×10 -3 ~1×10 -2 mol / L, this metal ion concentration can effectively promote oligomer polymerization.

[0053] Specifically, in some embodiments of the present invention, the concentration of catecholamines in the second catecholamine solution is 0.05 to 0.5 g / L, preferably 0.05 to 0.1 g / L.

[0054] Specifically, in some embodiments of the present invention, the fourth preset time is 0.5 to 8 hours, preferably 1 to 6 hours. The mixing temperature is room temperature (10 to 35°C). Preferably, in some embodiments of the present invention, the absorbent is an aqueous solution containing MDEA, and its MDEA content is ≥35wt%, and its activator content is ≥3.5wt%. Among them, the activator is piperazine, but not limited to this. The foam filler of the present invention effectively reduces the foaming height, so the content of MDEA and activator in the absorbent is further increased, thereby further improving the carbon capture efficiency. It should be noted that in conventional MDEA-based absorbents, the MDEA content is usually controlled to be ≤32wt%, and the activator content is ≤3wt% to reduce the foaming height.

[0055] Preferably, in some embodiments of the present invention, the absorbent is composed of the following components in weight percentage: 35-45% MDEA, 4-10% piperazine, 0.5-5% corrosion inhibitor, and the balance is water. Since the amount of activator piperazine used in the present invention is relatively high, the overall corrosion effect of the absorbent on the metal foam filler and the micro-filled bed reactor is also stronger. For this reason, the present invention also introduces 0.5-5% corrosion inhibitor. Specifically, the corrosion inhibitor can be sodium phosphate, potassium chromate, sodium nitrite, but is not limited thereto.

[0056] Specifically, in some embodiments of the present invention, the micro-packed bed is cylindrical, with an inner diameter of 5 to 20 mm, a length of 10 to 30 cm, and an aspect ratio of greater than or equal to 30.

[0057] Correspondingly, the present invention also discloses a reactor used in a carbon dioxide capture system, which is a micro-packed bed reactor, in which a foam filler is arranged. The foam filler is prepared by the above-mentioned method for preparing the foam filler.

[0058] Correspondingly, the present invention also discloses a reactor filler used in a carbon dioxide capture system, which is prepared by the above-mentioned preparation method of the foam filler.

[0059] The implementation of the present invention has the following beneficial effects:

[0060] The carbon dioxide capture system of the present invention introduces a micro-packed bed reactor, which has a high mass transfer efficiency and can effectively improve the capture efficiency of carbon dioxide. On the other hand, the micro-packed bed reactor of the present invention uses a foam filler prepared by a specific preparation method. Specifically, the present invention sequentially uses a first modified liquid obtained by mixing a first catecholamine solution with a buffer solution and a second modified liquid obtained by mixing inorganic nanoparticles, solvents, and fluorinated silane coupling agents to modify the metal foam. Based on the foam filler prepared by the above-mentioned preparation method, on the one hand, the hydrophobicity of the surface of the foam filler pores is greatly improved, and the gas-liquid mass transfer performance is enhanced; at the same time, the more hydrophobic pores can increase the liquid flow rate of the water film on the foam surface (i.e., the gas-liquid interface), reduce the foam stability, thereby reducing foaming and shortening the foaming time. Secondly, by forming inorganic nanoparticles of a specific particle size on the surface of the foam filler pores, the disturbance of the liquid flow distribution is improved, making the foam easier to eliminate, and controlling the particle size of the inorganic nanoparticles can also prevent excessive nanoparticles from accumulating and affecting the gas-liquid mass transfer performance. Third, by using catecholamine substances to organically adhere to the surface of the metal foam pores and composite inorganic nanoparticle coating, the mechanical stability of the entire coating is improved, and the acid and alkali resistance of the metal foam is improved, making it suitable for various types of carbon capture scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is an electron microscope image of the inner surface of the pores of the foam filler prepared in Example 2;

[0062] Figure 2 This is an electron microscope image of the inner surface of the pores of the foam filler in Comparative Example 1.

[0063] Figure 3 is an electron microscope image of the first intermediate after step (5) in Example 1 of the present invention;

[0064] Figure 4 This is an electron microscope image of the first intermediate after step (3) in Example 2 of the present invention. DETAILED DESCRIPTION

[0065] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0066] Example 1 Preparation of Foam Filler

[0067] (1) Metal foam nickel (average pore size of 155 μm) was placed in deionized water, anhydrous ethanol, and 0.2 M HCl in sequence, and ultrasonicated at 40 kHz for 30 min. It was then placed in deionized water and ultrasonicated at 40 kHz for 20 min. Finally, it was placed in a vacuum drying oven at 80 °C and dried for 4 h.

[0068] (2) dissolving 0.4 g of dopamine in 200 mL of deionized water, and adding 1.6 mL of tris(hydroxymethyl)aminomethane hydrochloric acid solution (0.5 mol / L) after the dissolution is complete to obtain a first modified solution;

[0069] (3) adding 4.5 g of the nickel foam obtained in step (1) to the first modified solution obtained in step (2), stirring and coating at 600 rpm for 20 h, rinsing with deionized water after coating, and finally placing in a vacuum drying oven at 60° C. and drying for 8 h to obtain a second intermediate;

[0070] (4) Dissolve 0.04 g of levodopa in 200 mL of deionized water. After the dissolution is complete, add ferrous chloride and cupric chloride to control the Cu 2+ , Fe 2+ The concentrations were 5×10 -3 mol / L and 3×10 -3 mol / L, and mix evenly to obtain a third modified solution;

[0071] (5) The second intermediate obtained in step (3) and the third modified liquid obtained in step (4) are mixed evenly, and after ultrasonic treatment for 30 minutes, the mixture is stirred and coated for 5 hours. After coating, the mixture is rinsed with deionized water, and finally placed in a vacuum drying oven at 60° C. and dried for 8 hours to obtain a first intermediate;

[0072] (6) adding 0.5 g of γ-alumina particles with an average particle size of 100 nm to 250 mL of an ethanol / water mixed solution, wherein the volume ratio of ethanol to water is 2:1, stirring at 500 rpm for 1 h, and then ultrasonically dispersing for 1 h to obtain a stable γ-alumina nanoparticle suspension; adding 2 mL of 17-fluorodecyltriethoxysilane to the γ-alumina nanoparticle suspension, stirring at 700 rpm for 20 min, to obtain a second modified solution;

[0073] (7) adding the first intermediate obtained in step (5) to the second modified solution obtained in step (6), performing grafting modification at 300 rpm for 6 hours, rinsing with deionized water after the modification is completed, and finally placing in a vacuum drying oven at 80° C. and drying for 6 hours to obtain a finished foam filler.

[0074] Example 2 Preparation of Foam Filler

[0075] (1) The copper foam (average pore size of 205 μm) was placed in deionized water, anhydrous ethanol, and 0.2 M HCl in sequence, and ultrasonicated at 40 kHz for 30 min. It was then placed in deionized water and ultrasonicated at 40 kHz for 20 min. Finally, it was placed in a vacuum drying oven at 80 °C and dried for 4 h.

[0076] (2) dissolving 0.4 g of levodopa in 200 mL of deionized water, and adding 2.4 mL of NaOH solution (0.8 mmol / L) after the dissolution is complete to obtain a first modified solution;

[0077] (3) adding 6.5 g of the copper foam obtained in step (1) to the first modified solution obtained in step (2), stirring and coating at 300 rpm for 24 h, rinsing with deionized water after coating, and finally placing in a vacuum drying oven at 60° C. and drying for 8 h to obtain a first intermediate;

[0078] (4) adding 1 g of silica particles with an average particle size of 20 nm to 400 mL of an ethanol / water mixed solution, wherein the volume ratio of ethanol to water is 4:1, stirring at 700 rpm for 1 h, and then ultrasonically dispersing for 0.5 h to obtain a stable silica nanoparticle suspension; adding 4 mL of heptadecafluorodecyltriethoxysilane to the silica nanoparticle suspension, stirring at 700 rpm for 20 min to obtain a second modified solution;

[0079] (5) adding the first intermediate obtained in step (3) to the second modified solution obtained in step (4), performing grafting modification at 300 rpm for 6 hours, rinsing with deionized water after the modification is completed, and finally placing in a vacuum drying oven at 80° C. and drying for 6 hours to obtain a finished foam filler.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a foam filler, which differs from Example 2 in that the preparation method does not include steps (2) to (5).

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing a foam filler, which differs from Example 2 in that the preparation method does not include steps (4) to (5), that is, the first intermediate is not grafted with the second modifying liquid.

[0084] Comparative Example 3

[0085] This comparative example provides a method for preparing a foam filler for a micro-packed bed reactor, which differs from Example 2 in that steps (2) to (3) are not included, i.e. the cleaned metal foam is directly coated with the second modifying liquid.

[0086] Example 3 Carbon dioxide capture system

[0087] This embodiment provides a carbon dioxide capture system, which includes:

[0088] The gas supply unit includes a raw gas cylinder and a gas phase branch: it is composed of a raw gas cylinder, a mass flow controller and a gas phase pressure sensor. It is used to introduce a mixed gas (17 vol% CO2 / 83 vol% N2 mixed gas) and control the introduction flow rate to be 100-300 sccm.

[0089] Absorbent supply unit: It consists of a liquid phase material bottle, a plunger pump and a liquid phase pressure sensor. It is used to introduce the absorbent, wherein the absorbent is composed of the following components in weight percentage: 42% MDEA, 8.5% piperazine, 1.2% sodium phosphate, and the balance is water. The flow rate is controlled to be 1-25mL / min, the liquid phase flow rate is controlled by the plunger pump, the pressure sensor measures the liquid phase pressure drop, and the paperless recorder displays the value.

[0090] A mixing unit, which is a T-type mixer;

[0091] The micro-packed bed reactor is filled with foam fillers. The micro-packed bed reactor is cylindrical, with an inner diameter of 6 mm and a length of 20 cm, and is filled with 40 foam fillers (the foam fillers are cylindrical, with a length of 5 mm and a diameter of 6 mm).

[0092] It should be noted that, in order to evaluate the foaming condition, a micro-packed bed reactor (cylindrical, 20 cm in length, 6 mm in inner diameter) made of transparent glass was used in the foaming experiment, with scales marked on its outer wall, and filled with 16 pieces of 5 mm long foam fillers (the foam fillers were cylindrical, 5 mm in length and 6 mm in diameter).

[0093] The foam fillers obtained in Examples 1 to 2 and Comparative Examples 1 to 3 were tested, and the specific test scheme is as follows:

[0094] (1) Test its contact angle;

[0095] (2) Filling the foam filler into the micro-packed bed reactor in Example 3 (completely filled), aerating the liquid to react, and calculating the mass transfer coefficient, energy efficiency, and carbon dioxide removal rate (reaction 50 s);

[0096] (3) Evaluation of foaming: The foam filler was filled into the glass micro-filled bed reactor in Example 3 (filler height 80 mm), and the reaction was allowed to ventilate. After the gas velocity stabilized, the timing was started. When the foaming height stabilized, the foam height was recorded, and the ventilation was stopped. The time when the foam burst and clear liquid was seen was the defoaming time.

[0097] (4) Stability evaluation: The foam fillers obtained in each example and comparative example were immersed in a HCl solution with a pH of 5.5 for 24 hours, and then the foaming conditions were evaluated.

[0098] The specific experimental data are shown in the following table:

[0099]

[0100] As can be seen from the above table, the foam filler of the present invention can effectively increase the contact angle of the foam filler, promote the unit removal rate of carbon dioxide in the carbon dioxide removal reaction, and improve the mass transfer coefficient and energy efficiency. At the same time, the foaming height is lowered and the defoaming time is shortened.

[0101] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A carbon dioxide capture system, characterized in that: include: A gas supply unit, used for providing a mixed gas containing carbon dioxide to be captured; An absorbent providing unit, used for providing an absorbent, wherein the absorbent is an amine absorbent; A mixing unit, used for mixing the mixed gas and the absorbent; and A micro-packed bed reactor filled with foam fillers; The preparation method of the foam filler comprises the following steps: (1) Providing metal foam; the metal foam is selected from one or more of nickel foam, iron foam, nickel copper foam, and copper foam, and the average pore size of the metal foam is 50-800 μm; (2) mixing the first catecholamine solution with a buffer solution to obtain a first modified solution; wherein the concentration of catecholamines in the first catecholamine solution is 0.5-5 g / L; and the catecholamines are selected from one or more of dopamine, levodopa, and norepinephrine; (3) mixing the first modified liquid and the metal foam in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a first preset time, and performing solid-liquid separation to obtain a first intermediate; (4) mixing the inorganic nanoparticles, the solvent and the fluorinated silane coupling agent for a second preset time to obtain a second modified solution; wherein the concentration of the inorganic nanoparticles in the second modified solution is 1-10 g / L, and the concentration of the fluorinated silane coupling agent is 0.2-2 vol%; the inorganic nanoparticles are selected from one or more of nano-silicon dioxide, nano-γ-alumina, nano-cerium oxide or nano-titanium dioxide, and the maximum particle size of the inorganic nanoparticles is ≤500 nm; (5) mixing the second modified liquid and the first intermediate in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a third preset time to obtain a foam filler; The corresponding relationship between parts by weight and parts by volume is g / mL.

2. The carbon dioxide capture system according to claim 1, wherein: The buffer solution is tris(hydroxymethyl)aminomethane hydrochloric acid solution or sodium hydroxide solution; and / or The solvent is selected from one or more of water, methanol, ethanol and propanol; and / or The silane coupling agent is selected from one or more of heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, or tridecafluorooctyltrimethoxysilane.

3. The carbon dioxide capture system according to claim 1, wherein: The metal foam is nickel foam, and its average pore size is 150-300 μm; and / or The average particle size of the inorganic nanoparticles is 10 to 200 nm; and / or The catecholamine is levodopa; and / or The buffer solution is sodium hydroxide solution; and / or The inorganic nanoparticles are nano-γ-alumina; and / or The solvent is a mixture of water and ethanol, and the volume ratio of water to ethanol is 2-4:1; and / or The silane coupling agent is heptadecafluorodecyltrimethoxysilane.

4. The carbon dioxide capture system according to claim 1 or 3, characterized in that In step (1), the metal foam is washed with water, ethanol, hydrochloric acid and water in sequence; and / or In step (2), the concentration of catecholamines in the first catecholamine solution is 1.5-3 g / L; and / or In step (3), the first modified liquid and the metal foam are mixed in a ratio of 200-400 parts by volume: 4-9 parts by weight, stirred and immersed at a speed of 300-900 rpm for 6-48 hours, and the solid phase obtained after solid-liquid separation is washed with water and dried to obtain a first intermediate; and / or In step (4), the inorganic nanoparticles and the solvent are mixed at a speed of 500-900 rpm for 1-2 hours, and ultrasonically dispersed for 0.5-1 hour, and then a silane coupling agent is added and mixed at a speed of 500-900 rpm for 10-30 minutes to obtain a second modified liquid; and / or In step (5), the second modified liquid and the first intermediate are mixed in a ratio of 200-400 parts by volume: 2-7 parts by weight, and grafted at a rotation speed of 300-700 rpm for 2-10 hours. After solid-liquid separation, the obtained solid phase is washed with water and dried to obtain a foam filler; The corresponding relationship between parts by weight and parts by volume is g / mL.

5. The carbon dioxide capture system according to claim 1, characterized in that Step (3) includes: (3.1) mixing the first modified liquid and the metal foam in a ratio of 100 to 500 parts by volume: 1 to 10 parts by weight for a first preset time, and performing solid-liquid separation to obtain a second intermediate; (3.2) Mixing the second catecholamine solution with the metal salt to obtain a third modified solution; wherein the concentration of catecholamines in the second catecholamine solution is 0.05-0.5 g / L, and the concentration of metal ions is 5×10 -4 ~1×10 -2 mol / L; the metal ion is Fe 2+ , Fe 3+ , Cu 2+ 、Zn 2+ One or more of; (3.3) mixing the third modified liquid and the second intermediate in a ratio of 100-500 parts by volume: 1-10 parts by weight, ultrasonically treating for a fourth preset time, and performing solid-liquid separation to obtain a first intermediate; The corresponding relationship between parts by weight and parts by volume is g / mL.

6. The carbon dioxide capture system according to claim 1, characterized in that The absorbent is an aqueous solution containing MDEA, wherein the MDEA content is ≥35wt% and the activator content is ≥4wt%.

7. The carbon dioxide capture system according to claim 1 or 6, characterized in that The absorbent is composed of the following components in weight percentage: MDEA 35~45%, piperazine 5~10%, corrosion inhibitor 0.5~5%, and the balance is water.

8. The carbon dioxide capture system according to claim 1, characterized in that The micro-packed bed is cylindrical, with an inner diameter of 5-20 mm, a length of 10-30 cm, and an aspect ratio of greater than or equal to 30.

9. A reactor for use in a carbon dioxide capture system, characterized in that: It is a micro-packed bed reactor with foam fillers inside. The foam filler is prepared by the method for preparing the foam filler as claimed in claim 1.

10. A reactor packing for a carbon dioxide capture system, characterized in that: The foam filler is prepared by the method for preparing the foam filler as claimed in claim 1.

Citation Information

Patent Citations

  • Composite decarbonization solvent for eliminating carbon dioxide in natural gases

    CN101822932B

  • Method for strengthening mixing and reaction of fluids in micro-reactor

    CN105617957A

  • Preparation method of photocatalytic air purification material

    CN108465461A